Effect of NPK fertilizers on the initial growth of transplanted seedlings of Butia eriospatha - Lima, Carlos Fellipe Meurer de; Flores, Andressa Vasconcelos; Laurindo, Lídia Klestadt; Menegussi, Milena; Oliveira, Heloisa Maria de; Oliveira, Luciana Magda de; Júnior, Paulo Cesar Flores (Revista de Ciências Agroveterinárias, 2024)
Butia eriospatha (Martius ex Drude) Beccari is a palm tree endemic to the southern region of Brazil, of economic and cultural value. Currently, the species is classified as endangered, due to agricultural expansion, urbanization and difficulties in propagating the species. The objective of this study was to evaluate the effect of NPK fertilizers on the initial growth of transplanted seedlings of B. eriospatha. The seedlings were obtained from a natural regeneration area in the municipality of Curitibanos (SC), and transplanted to 2.6 L pots containing Carolina Soil® commercial substrate. The experiment was carried out in a greenhouse in a completely randomized design. To analyze the effect of fertilizers, seven treatments were used, namely the application of nitrogen (N), phosphorus (P), potassium (K), nitrogen, phosphorus and potassium (NPK), phosphorus and nitrogen (PN), nitrogen and potassium (NK) and phosphorus and potassium (PK), containing 20 replicates each and totaling 140 seedlings. The fertilizers used in the experiment were urea, triple superphosphate and potassium chloride, applied every two weeks. Every two months, the neck diameter and stem height were evaluated for 22 months. The best treatment for the biometric growth of B. eriospatha seedlings transplanted to Carolina Soil® commercial substrate was the association of phosphorus and nitrogen.